Pengetahuan, Gangguan Psikologis, dan Burnout Dokter Umum di Era Pandemi Covid-19 - Alfian Nur Rosyid; Arina Dery Puspitasari; Tamara Nur Budiarti; Izzatul Fitriyah; Anggraini Dwi Sensusiati; Muhammad Amin (Jurnal Pengabdian Pada Masyarakat, 2021)
KNOWLEDGE, PSYCHOLOGICAL DISORDERS, AND BURNOUT OF GENERAL PRACTITIONERS IN THE COVID-19 PANDEMIC ERA. High demand in work during the Covid-19 pandemic will cause psychological problems for general practitioners. These psychological disorders can cause burnout. The incidence of burnout is exacerbated by the lack of knowledge of general practitioners about the current condition. This study aims to determine the level of knowledge, psychological disorders, and burnout of general practitioners during the Covid-19 pandemic. The research design using quasi-experimental with one group pre posttest design without a control group. The population in this study was all participants that join the online seminar. Samples taken were 111 respondents with the total sampling technique. The data collection technique was done by using a questionnaire. The data obtained were analyzed using the Wilcoxon test and Kendall's tau-c test. The difference test before and after being given the seminar material shows a p-value of 0.001. The statistical analysis of the relationship between knowledge and burnout shows a p-value of 0.048. The statistical analysis of the relationship between stress and burnout shows a p-value of 0.026. The statistical analysis of the relationship between anxiety and burnout shows a p-value of 0.001. The statistical analysis of the relationship between depression and burnout showed a p-value of 0.002. There are differences in the knowledge of respondents before and after being given the seminar material. There is an association between knowledge with burnout, stress with burnout, anxiety with burnout, and depression with burnout.